Solar radiation leads to increased collagenase gene expression (MMP1) in HERDA (Hereditary equine regional dermal asthenia) affected horses and may explain the typical dorsal distribution of their lesions - da Cunha Neto, Campo Amor Vieira [UNESP]; Badial, Peres Ramos; de Oliveira-Filho, José Paes [UNESP]; de Andrade, Danilo Giorgi Abranches [UNESP]; Araujo Jr, João Pessoa [UNESP]; Borges, Alexandre Secorun [UNESP] (Wiley, 2022)
Background: Hereditary equine regional dermal asthenia (HERDA) is a genetic disease that alters collagen biosynthesis. Affected horses exhibit fragile, hyperextensible skin, especially over the dorsal region. Although ultraviolet (UV) radiation seems to contribute to the regional distribution of lesions and worsening of clinical signs, the molecular mechanisms involved are largely unknown. Objectives: To evaluate the effect of solar radiation on matrix metalloproteinase MMP1, MMP8 and MMP13 gene expression in the dorsal and ventral skin of HERDA-affected and HERDA-unaffected horses [wild-type (WT) horses]. Animals: Six HERDA-affected and six unaffected Quarter horses (WT) were paired according to age, sex and coat colour. Materials and methods: Horses were submitted to 30 day sunlight restriction, followed by 15 day sunlight exposure. Dorsal and ventral skin biopsies were obtained at six sampling times over 45 days. The expression of MMP1, MMP8 and MMP13 genes was measured by quantitative PCR. Results: Although solar radiation modulated MMP1, MMP8 and MMP13 expression, the effects were more pronounced on MMP1. Sun exposure for three days significantly upregulated MMP1 in the dorsal region when compared to the ventral skin in both unaffected and HERDA-affected horses. Conclusions and clinical relevance: This study shows that solar irradiation leads to upregulation of skin collagenase genes particularly MMP1 in the dorsal, sun-exposed skin of horses. Furthermore, this was more marked in HERDA-affected horses. The increased activity of collagenases on the disorganised collagen present in HERDA affected horses would explain why UV radiation leads to deterioration of clinical signs in affected individuals.